Proceedings of SPE Hydraulic Fracturing Technology Conference 2007
DOI: 10.2523/106289-ms
|View full text |Cite
|
Sign up to set email alerts
|

Shear Dilation Diagnostics: A New Approach for Evaluating Tight Gas Stimulation Treatments

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractMany tight gas reservoirs require fracture stimulation to achieve commercial outcomes. These reservoirs can often be characterized geologically and geomechanically by high deviatoric stresses and hard, naturally fractured rock. Stimulation treatments in such reservoirs may create complex fracture networks from a combination of shear and tensile failures. Water fracs can be used where shear failure is anticipated to dominate. However, in these environments few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…During hydraulic fracturing, Chipperfield et al proposed that the initiation and propagation of fractures formed tensile fractures and caused shear deformation. 17 Fluid injection-induced aseismic slip of faults and surface ruptures were proposed by Wei et al 18 Based on the analysis of microseism data, Qian et al observed that the casing deformations in the Sichuan basin occurred primarily due to shear slips in the large-scale natural fracture areas. 19 Bao and Eaton suggested that different mechanisms could trigger fault activation during and after hydraulic fracturing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During hydraulic fracturing, Chipperfield et al proposed that the initiation and propagation of fractures formed tensile fractures and caused shear deformation. 17 Fluid injection-induced aseismic slip of faults and surface ruptures were proposed by Wei et al 18 Based on the analysis of microseism data, Qian et al observed that the casing deformations in the Sichuan basin occurred primarily due to shear slips in the large-scale natural fracture areas. 19 Bao and Eaton suggested that different mechanisms could trigger fault activation during and after hydraulic fracturing.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, recently, several researchers have explored the shear deformation caused by fault slides during hydraulic fracturing. During hydraulic fracturing, Chipperfield et al proposed that the initiation and propagation of fractures formed tensile fractures and caused shear deformation . Fluid injection-induced aseismic slip of faults and surface ruptures were proposed by Wei et al Based on the analysis of microseism data, Qian et al observed that the casing deformations in the Sichuan basin occurred primarily due to shear slips in the large-scale natural fracture areas .…”
Section: Introductionmentioning
confidence: 99%